Clinical management of confluent canals - Gianluca Gambarini; Ivona Bago; Adrianna Adamek-Mrozowska; Byron Tsivos (Annali di Stomatologia)
Confluent canals are potentially dangerous for endodontic rotary instruments because they are rarely detected with periapical radiographs and they usually create an abrupt curvature, with a small radius less than two millimeters and a high degree of the curvature close up to 90 degree. The purpose of this clinical article is to show first how to manage this confluent canal according to the Vertucci technique, and also provide some clinical guidelines about determining if a confluence is present or not, at which level and which is the working length for each instrument, and which is the canal to be instrumented first. If all these recommendations are correctly followed, a very common and dangerous clinical problem for endodontists can be very easily and quickly resolved, significantly reducing the risk of intracanal failures without any additional special devices but only by using knowledge and clinical skills